Avaliação do potencial fotoprotetor do extrato hidroalcoólico de Lafoensia pacari A. St-Hill (Lytraceae) e obtenção de uma formulação fitocosmética - Caixeta, Eliane de Vasconcelos (2014)
In Brazil, the number of cases of skin cancer has increased, representing a significant public health problem. Various cosmetic products have been developed with sunscreens and from marketing’s point of view the addition of natural products in particular containing phenolic compounds, has been the subject of several studies. The aim of this study was to determine the Sun Protection Factor (SPF) of hydroalcoholic Lafoensia pacari extract and assess its potential for additive in SPF in a sunscreen formulation containing the chemical filter metoxycinamate octyl. First it was obtained hydroalcoholic L. pacari extract and the monitoring of extraction process by CCD. The SPF from L. pacari extract, from the chemical filter metoxycinamate octyl (eusolex 2292®) and both formulations were determined using the technique of Mansur and colleagues with adaptations, such as diffuse reflectance.The chromatographic profile of the extract or formulation were investigated by CLAE as well as dosing of total phenols and flavonoids. In addition, tests for antioxidant activity of the extract by DPPH and FRAP methods were carried out. Lastly, it was performed the accelerated stability on a 90-day cycle formulation at three different temperature conditions. Regarding the chromatographic profile by CCD it was detected seven stains in the four extraction conditions employed, being eluted identically and after revealed by NP, they were indicative of polyphenols and flavonoids. It was selected the extraction by bath of 30 min ultrasound. The formulation containing eusolex 2292® and extract achieved a 7.3 indicating activation and photoprotection. Using a reflectance technique, the achieved results were from 9.7 to 11.11, confirming the additive by a more sensitive technique. The chromatographic profiles, by CLAE, the extract or formulation showed peaks with retention times and identical UV absorption spectrum, thereby confirming the presence of the extract in the final formulation. Dosing of total phenols resulted in 3.31% and total flavonoids 0.31%. Antioxidant activity by DPPH assay showed EC50 = 53,73 mg/L and FRAP results showed that 1 g of Pacari extract showed reduction capability of 323.62 μM of ferrous sulfate. The preliminary stability test showed that there was a formulation stability in the FPS and viscosity after freeze - defrost cycle.It was found that the extract obtained from the leaves of L. pacari has absorbance in UVC, UVB and UV. This extract was able to aditivar FPS formulation developed in this work, containing eusolex 2292® chemical filter and showed antioxidant activity .